Efek Program Video Oberseved Therapy (VOT) Terhadap Kepatuhan Treatment Pada Penderita Tuberculosis - Devita Anugrah Anggraini; Meira Erawati; Andrew Johan (STIKES Karya Husada Kediri, 2021)
Introduction : The government recommended the Directly Observed Therapy (DOTS) program to adjust the treatment of tuberculosis. The rapid used of mobile phones provides access to health programs in the community. Video Observed Therapy (VOT) may be effective as a medium of communication with health care providers who can assisted and supported patients to completed TB treatment care that requires ongoing commitment from remoted observation. This review is to found out the implementation of the Video Observed Therapy (VOT) program on Treatment Compliance in Tuberculosis Patients. Method: The method used is Scoping review through 11 articles in the span of 8 years 2012 and 2020. Results and discussion: Based on the results of data analysis and discussion of the above research regarding the application of nursing research related to the therapeutic video observation (VOT) program in improving tuberculosis treatment adherence. So it should be said that the results of the study are to proved that the VOT program has the potential as an observation of treatment programs (DOT) and should improved patient compliance in TB treatment and other results such as from the aspect of acceptability, as well as the feasibility of costs. Conclusion: Patient adherence to the tuberculosis treatment program could be improved through DOTS observation used video intervention therapy observation.